Coexistence of Cardiovascular and Renal Disease: A Study on Burden of Cardiorenal Syndrome in a Tertiary Care Hospital in Bangladesh (Community Based Medical Journal, 2026)
Cardiorenal syndrome (CRS) represents a complex, bidirectional interplay between cardiac and renal dysfunctions, leading to significantly increased morbidity, mortality, and healthcare burden. The epidemiological data on its prevalence and pattern in Bangladesh are scarce. A prospective, cross-sectional study was conducted in Community Based Medical College, Bangladesh (CBMC,B) Hospital, Mymensingh, Bangladesh, from June 2024 to July 2025, to determine the burden and characterize the profiles of patients with CRS. A purposive sample of 123 adult inpatients presenting with concomitant cardiovascular and renal disease got enrolled in the study. Data on demographics, clinical profiles, laboratory investigations, and echocardiographic findings were collected using a structured case record form. The CRS was classified into five subtypes based on established consensus definitions. The mean age was 62.4±10.7 years with male predominance (64.2%). Hypertension (88.6%) and diabetes mellitus (72.4%) were the most common comorbidities. Type 1 Cardiorenal Syndrome (41.5%) was most prevalent. Heart failure with reduced ejection fraction was common (58.5%). Anemia (78.0%) and hyperuricemia (65.0%) were frequent complications. In-hospital mortality was 12.2%, significantly associated with higher creatinine, lower eGFR, and elevated NT-proBNP levels (p